2009
DOI: 10.1001/archneurol.2009.5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of N-methyl-D-aspartate Receptor Antibodies in Women With New-Onset Epilepsy

Abstract: Background: In women younger than 45 years, a new form of encephalitis associated with ovarian teratoma and presenting with seizures and psychiatric symptoms has been described. Most patients have antibodies to NR1/ NR2 heteromers of the N-methyl-D-aspartate receptor (NMDAR). Objective: To assess the frequency and significance of antibodies to NMDAR in otherwise unexplained newonset epilepsies in young women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(114 citation statements)
references
References 28 publications
(22 reference statements)
3
105
0
6
Order By: Relevance
“…Complete recovery in the absence of immunotherapy has been reported in patients with anti-NMDAR encephalitis and emphasizes the concept that autoimmune synaptic encephalitides are underdiagnosed. 23 In this study, all patients with concurrent GABA B R-ab and GAD-ab had a paraneoplastic neurologic disorder. In the initial series, 2 of the 8 patients with idiopathic LE encephalitis had additional GAD-ab.…”
Section: Resultsmentioning
confidence: 78%
“…Complete recovery in the absence of immunotherapy has been reported in patients with anti-NMDAR encephalitis and emphasizes the concept that autoimmune synaptic encephalitides are underdiagnosed. 23 In this study, all patients with concurrent GABA B R-ab and GAD-ab had a paraneoplastic neurologic disorder. In the initial series, 2 of the 8 patients with idiopathic LE encephalitis had additional GAD-ab.…”
Section: Resultsmentioning
confidence: 78%
“…Varying rates of tumour presence at diagnosis of NMDAR encephalitis have been recorded. Dalmau et al reports this to be about 25% 9 while others report much lower rates 21,22 . Florence et al studying 81 patients found that 30% of women younger than 18 years, and less than 10% of girls younger than 14 years had tumours 12 .…”
Section: Association With Neoplasmsmentioning
confidence: 95%
“…There is some data to show that children may have better outcome than adults with full recovery seen in above 70% 10 . Early immunosuppressive therapy and prompt tumour removal appears to favourably affect the outcome 18,21,27 . Even when treated, deficits and even death may not be avoidable in some 6,18,27 .…”
Section: Disease Modifying Therapymentioning
confidence: 99%
“…Another typical feature of the anti-NMDAR encephalitis, episodic memory impairment, can be modeled by suppressing long-term potentiation through antibodies [81]. However, the frequent occurrence of seizures [82], and even status epilepticus [83], is not easily explained by an NMDAR hypofunction, as NMDAR blockers exert an antiepileptic effect and have been considered as treatment option in status epilepticus [84].…”
Section: Antibodies Against Nmdarmentioning
confidence: 99%